2016
DOI: 10.1007/s00405-016-4434-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of speech perception in quiet and in noise without decreasing localization abilities with the bone conduction device Bonebridge

Abstract: The aim of this study was to examine the functional hearing results regarding speech perception and auditory sound localization in a high-resolution directional hearing setup following implantation with a new bone conduction device (MED-EL Bonebridge, Innsbruck, Austria). In addition, we assessed the patient acceptance of the Bonebridge system using a questionnaire. The study design is retrospective study. The setting is University Hospital Frankfurt. 18 patients implanted with a Bonebridge device from May 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 15 publications
9
23
1
5
Order By: Relevance
“…As far as we know, there have no previously published reports that have applied and compared the Speech, Spatial and Qualities (SSQ). However, in contrast with the findings of Weiss et al, [ 41 ], the two patients reported, showed an improvement in spatial localization with the Bonebridge BCI system, but this finding was less prominent than the increase in perception of speech and noise and the quality of the perceived sound. However, the use of subjective patient questionnaires for treatment response is a limitation in the assessment of the responses to the use of the Bonebridge BCI system in these two cases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As far as we know, there have no previously published reports that have applied and compared the Speech, Spatial and Qualities (SSQ). However, in contrast with the findings of Weiss et al, [ 41 ], the two patients reported, showed an improvement in spatial localization with the Bonebridge BCI system, but this finding was less prominent than the increase in perception of speech and noise and the quality of the perceived sound. However, the use of subjective patient questionnaires for treatment response is a limitation in the assessment of the responses to the use of the Bonebridge BCI system in these two cases.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, no specific rehabilitation was needed, and soon after activation and fitting of the audio processor, both patients were able to understand a conversation, even in a non-native language. Importantly, the functional gain in hearing following implantation was comparable to previously published cases in the literature in terms of pure-tone thresholds (+39.25 vs. +26.1±13.7; 29.3±20.7) [ 40 , 41 ], whereas speech recognition scores were higher(100% at +70 dB, vs. +36.25 dB and 95% at +21%) [ 28 ]. The 2.5 dB hearing loss and 3.5 dB hearing loss bone conduction improvement observed in both cases was not surprising, given the known Carhart effect due to stapes ankylosis in congenital middle ear malformation [ 42 ].…”
Section: Discussionsupporting
confidence: 80%
“…The preoperative and postoperative results can be seen in the S2 Table. Speech understanding in quiet was assessed in 27 publications [16, 26, 27, 7, 28, 22, 29, 24, 30, 10, 31, 25, 3234, 18, 12, 13, 35, 36, 20, 14, 37, 38, 21, 39], resulting in a mean unaided WRS score of 25.73±23.64% improving to 84.48±15.09% in the aided condition, resulting in an overall mean improvement of almost 60% (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Results for speech in noise tests could not be compared directly in a meta-analysis due to the individual test set-up and inconsistency in reporting for the different studies. However, an improvement in speech understanding in noise was observed with the atBCI in all studies for subjects with CHL or MHL (S2 Table) [23, 8, 13, 20, 38, 21].…”
Section: Resultsmentioning
confidence: 99%
“…Our audiological results are in line with previous studies [ 4 , 13 , 14 , 23 , 24 , 26 , 27 , 30 , 35 , 36 ]. The mean gain in speech understanding was very high compared to the results in other studies, which also used the German monosyllabic Freiburger test at 65 dB [ 23 25 , 29 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%